Analisis Urutan Fasa dan Arus Start pada Mode Forward Motor Induksi Tiga Fasa dengan Starter Direct Online dan Star-Delta - Wiwit Santoso; Wawan Gunawan; Yogi Priyo Istiyono; Aripin Triyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Three-phase induction motors have the drawback of high starting currents, reaching 5 to 7 times the rated current, which can potentially interfere with other equipment on the same circuit. This study aims to design a trainer kit, analyse phase sequences, and compare the starting currents of three-phase induction motors using the DOL and Star-Delta starting methods in forward mode. The experimental method was implemented by assembling a trainer kit with components such as an MCB, contactor, TOR, and TDR. Testing involved measuring the phase sequence using a Phase Rotation Tester and the starting current using an ampere clamp with varying DC injection braking loads of 0–200 VDC. The results show that the trainer kit functions optimally, with the phase sequence of the power source and the motor in forward mode (R-S-T) rotating clockwise (CW). In the analysis of starting current, the Star-Delta starting method was shown to significantly reduce current surges compared to the DOL starting method. Under no-load conditions at 0 VDC, the Star-Delta method reduced the starting current by 65.98%, from 0.97 A to 0.33 A. However, at a maximum load of 200 VDC, the reduction effectiveness decreased to 31.10%, from 2.99 A to 2.06 A. Star-Delta starting is highly effective at reducing starting current, although its effectiveness decreases as the motor’s mechanical load increases.